Sterols and triterpene from Trichosanthes kirilowii - Vinh, Bui Hoang; Trang Tho, Pham Thi; Tai, Bui Huu; Tuan Anh, Hoang Le; Trung, Trinh Nam; Dung, Hoang Viet; Ban, Ninh Khac; Minh, Chau Van; Kiem, Phan Van; Nhiem, Nguyen Xuan (Vietnam Journal of Chemistry, 2015)
By various chromatographic methods, two sterols and one triterpene, 22E,24Z-stigmasta-7,22,24(28)-triene-3β-ol, ergosta-6,22-diene-3β,5α,8α-triol, and 3β-hydroxymultiflora-8-ene-17-oic acid were isolated from the roots of Trichosanthes kirilowii MAXIM. Their structures were elucidated by spectroscopic methods and in comparison with the reported data. To our best knowledge, compound 1 was isolated from the nature for the first time. Compounds 2 and 3 were reported from Trichosanthes genus for the first time.